Camp‐based multi‐component intervention for families of young children with type 1 diabetes: A pilot and feasibility study. Issue 4 (15th December 2017) - Gupta, Olga T; MacKenzie, Marsha; Burris, Angie; Jenkins, Bonnie B; Collins, Nikki; Shade, Molly; Santa‐Sosa, Eileen; Stewart, Sunita M; White, Perrin C
Abstract : Background: Managing type 1 diabetes mellitus (T1DM) in preschool‐aged children has unique challenges that can negatively impact glycemic control and parental coping. Objective: To evaluate the impact of a camp‐based multi‐component intervention on glycated hemoglobin A1c (HbA1c) in young children with T1DM and psychosocial measures for their parents. Subjects and methods: Two separate cohorts of 18 children (ages 3‐5 years) and their families participated in a camp‐based intervention that included didactic and interactive parent education, child‐centered education and family‐based recreational activities. In Camp 1.0, measures of HbA1c, parental fear of hypoglycemia, mealtime behaviors and quality of life (QOL) were compared before and after an initial session (I) and follow‐up booster session (II) 6 months later. Based on these results, the intervention was consolidated into 1 session (Camp 2.0) and repeated with additional measures of parental stress and parental self‐efficacy with diabetes management tasks. Results: Participants in Camp 2.0 exhibited a significant decrease in mean HbA1c level (−0.5%, P  = .002) before and after camp. Mothers exhibited a significant improvement in diabetes‐specific QOL (Camp 1.0/Session I and Camp 2.0) and reduction in stress as measured on the Pediatric Inventory for Parent (PIP) assessment (Camp 2.0). The booster session in Camp 1.0 showed no added benefit. Conclusions: A family centered, camp‐based multi‐component intervention in young children with T1DM improved HbA1c and perceived QOL and stress in their mothers.